Determinasi Pengetahuan Kewirausahaan, Self Efficacy, Inovasi terhadap Social Entrepreneurship Mahasiswa Wirausaha - Indri Murniawaty; Nina Farliana; Ahmad Sehabuddin; Reifi Apsarining Tyas (UM Purwokerto Press, 2022)
This study aimed to analyze the effect of entrepreneurial knowledge, self-efficacy and innovation on social entrepreneurship in student members of the Indonesian Young Entrepreneurs Association (HIPMI) Universitas Negeri Semarang. The research used is quantitative method. The research population is all entrepreneurial students who are members of Universitas Negeri Semarang HIPMI class 2019-2020. The total of samples as many as 83 respondents with the technique of determining the saturated sample. The collecting data method using a questionnaire. The data analysis method used is descriptive analysis and multiple regression analysis through the SPSS 21 program. The results show that the variables of entrepreneurial knowledge, self-efficacy, and innovation simultaneously affect social entrepreneurship by 65.3%. While partially self-efficacy has the greatest effect on social entrepreneurship by 15.9%, entrepreneurial knowledge has an effect of 9.20%, and innovation has an effect on social entrepreneurship by 6.90%. The variables of entrepreneurial knowledge, self-efficacy, and innovation simultaneously affect social entrepreneurship. Suggestions given to entrepreneurial students are expected not only to be entrepreneurship that prioritizes profit, but also to have a social mission. Suggestions for further researchers to examine research on social entrepreneurship using other variables.